JURIDICAL ANALYSIS OF FUNCTIONS AND BENEFITS OF VILLAGE COMMUNITY INSTITUTIONS IN TANJUNGPINANG CITY - Syaputra, Roni; Parroha Patar Siadari, Lagat; Fadlan, Fadlan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the implementation of the functions and benefits of urban village social institutions in Tanjungpinang City in order to guarantee and provide legal certainty to the community so that they can be legally accounted for, especially when accountability is in accordance with statutory regulations. The problems in this research are First; functions and benefits of village community institutions in Tanjungpinang City? Second, how are the efforts to supervise village community institutions in Tanjungpinang City? Third; What are the factors constraining the development of village community institutions in Tanjungpinang City. This research uses a descriptive method with the type of empirical or sociological normative research (applied law research) which is basically a merger with a normative approach (legal research), namely legal research regarding the application or implementation of normative legal provisions (codifications, laws or contracts) as a whole. in action on certain legal events that occur in society and in order to obtain primary data through field research (research). Based on the results of the research, it was found that the legal arrangements for Social Institutions were adequate as regulated in the Regulation of the Minister of Home Affairs Number 18 of 2018 concerning Social Institutions and Tanjungpinang City Regional Regulation Number 10 of 2021 concerning Community Institutions. Second, in supervising community institutions to pay more attention to the implementation of duties, functions and obligations in social institutions. Third, the constraints/obstacles on community participation and socialization which should be the government's reference for increasing the welfare of the people in the Kelurahan in particular and in the City of Tanjungpinang in general.